2015
DOI: 10.1248/cpb.c15-00106
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Anticancer Activity of Novel <i>Pulsatilla</i> Saponin D Analogues

Abstract: Novel saponins that retain a free carboxyl group at the C-17 position and various sugars linked at the C-3 position of hederagenin aglycone were synthesized via stereospecific glycosylation. Since these natural products represented by Pulsatilla saponin D (PSD) were obtained in very small amounts, the total synthesis developed in this paper will resolve this problem of scarcity. The two types of synthesized arabinose-and rhamnose-cored saponins showed potent anticancer activity against a human lung cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…H6, derived from HED, may improve the antitumor action of paclitaxel . HED saponins (such as macranthoside B), triterpene saponin compound 8, and Pulsatilla saponin D analog (compound 10i) exhibit antitumor effects. It was indicated that the sugar structures (i.e., α-hederin) of triterpenoid saponins are closely related to their anticancer properties . HED and its analogs have potential anticancer effects; however, the efficiency of HED is poor, with the underpinning anticancer mechanism remaining unclear.…”
Section: Introductionmentioning
confidence: 99%
“…H6, derived from HED, may improve the antitumor action of paclitaxel . HED saponins (such as macranthoside B), triterpene saponin compound 8, and Pulsatilla saponin D analog (compound 10i) exhibit antitumor effects. It was indicated that the sugar structures (i.e., α-hederin) of triterpenoid saponins are closely related to their anticancer properties . HED and its analogs have potential anticancer effects; however, the efficiency of HED is poor, with the underpinning anticancer mechanism remaining unclear.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the existing literature shows that PC saponins can make glycolysis key proteins ERK1/2, hypoxia-inducible factor-1α (HIF-1a), Ras, glucose transporter 1 (GLUT1), lactate transporter (MCT4), Hexokinase 2 (HK2), MCT1, c-Myc and other factors were significantly reduced ( 91 ). The results showed that PC saponins can regulate the energy metabolism of tumor cells through the HIF-1α pathway to achieve the effect of inhibiting tumor growth ( 66 ).…”
Section: Anti−tumor Effectsmentioning
confidence: 99%
“…10 Novel analogues of 1, including some with various sugar moieties linked at the C-3 position of hederagenin, have been synthesized, but did not show improved cytotoxicity. 11 In recent years, our group has reported new triterpenoid saponins modified at the C-28 COOH substituent with amide, ester, or nitric oxide (NO) donating groups. Moreover, some derivatives exhibited dramatically decreased hemolytic toxicity accompanied by potent tumor growth inhibition against murine H22 hepatocellular cells in vivo.…”
mentioning
confidence: 99%
“…Moreover, some derivatives exhibited dramatically decreased hemolytic toxicity accompanied by potent tumor growth inhibition against murine H22 hepatocellular cells in vivo. 1215 In light of the above results, 1115 new structure−activity relationship (SAR) correlations and structure−toxicity relationship (STR) correlations of 1 were explored in this report. First, new derivatives of 1 with a modified C ring were designed and synthesized (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation